2019
DOI: 10.18502/pbr.v5i1.761
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of curcumin against aluminum chloride-induced oxidative stress and hepatotoxicity in rats

Abstract: Aluminum is recognized as a public health concern because of its potential toxic effects on human health. Therefore, the present experiment was undertaken to determine the effectiveness of curcumin (CUR) in reducing the hepatotoxicity induced by aluminum chloride (AlCl3) in animals. In this experimental study, forty male rats were allocated to five groups (N = 8), viz. no treatment (control), solvent (DMSO or distilled water), CUR (10 mg/kg B.W.), AlCl3 (10 mg/kg B.W.), and CUR+AlCl3 (each with 10 mg/kg B.W.).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 0 publications
4
8
0
Order By: Relevance
“…Furthermore, increased enzymatic activity of alkaline phosphatase (ALP) in the blood generally describes primary liver biliary cirrhosis or an alteration of the hepatic architecture [49], since the rise in total bilirubin level might be due to erythrocyte haemolysis or disruption of hepatic function [2]. Remarkable AlCl 3 -induced alterations in biochemical parameters (decreased plasma concentrations of total proteins and albumin and increased AST, ALT and PAL activities) were confirmed by the These results are in line with those previously reported [14,21].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Furthermore, increased enzymatic activity of alkaline phosphatase (ALP) in the blood generally describes primary liver biliary cirrhosis or an alteration of the hepatic architecture [49], since the rise in total bilirubin level might be due to erythrocyte haemolysis or disruption of hepatic function [2]. Remarkable AlCl 3 -induced alterations in biochemical parameters (decreased plasma concentrations of total proteins and albumin and increased AST, ALT and PAL activities) were confirmed by the These results are in line with those previously reported [14,21].…”
Section: Discussionsupporting
confidence: 83%
“…We demonstrated that the decrease in the levels of protein transporters is associated with liver tissue damage, as evidenced by a significant increase in AST, ALT and LDH activity. This finding could support the hepatic histopathological modifications found, resulting in leakage of liver enzymes into the bloodstream following alterations in cell membrane permeability [48,14]. Furthermore, increased enzymatic activity of alkaline phosphatase (ALP) in the blood generally describes primary liver biliary cirrhosis or an alteration of the hepatic architecture [49], since the rise in total bilirubin level might be due to erythrocyte haemolysis or disruption of hepatic function [2].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…It had been reported that the accumulation of AlC1 3 in the liver tissue is associated with necrosis and degeneration of hepatic tissue to escape of liver enzymes from the injured cells to the plasma (Imam et al, 2016;Yousef, 2004). In addition, histological changes in the liver and the increase of plasma enzyme activities may be due to free radicals production and oxidative stress after AlC1 3 administration in the liver tissue (Abdel-Wahab, 2012; Cheraghi & Roshanaei, 2019). On the other hand, the administration of propolis, AlCl 3 combined with propolis and administration of AlCl 3 for 1 month, and administration of AlCl 3 combined with propolis for another month showed non- no inflammatory cells were detected as compared to aluminum treated group (d).…”
Section: Discussionmentioning
confidence: 99%
“…Group II (AlCl 3 group): Rats were received 10 mg/ kg b.w in 0.2 ml of AlCl 3 once daily through oral gavage 14 .…”
Section: Methodsmentioning
confidence: 99%